Targeting Lysosomes in Cancer as Promising Strategy to Overcome Chemoresistance—A Mini Review - Geisslinger, Franz; Müller, Martin; Vollmar, Angelika M.; Bartel, Karin (Frontiers in Oncology, 2020)
To date, cancer remains a worldwide leading cause of death, with a still rising incidence. This is essentially caused by the fact, that despite the abundance of therapeutic targets and treatment strategies, insufficient response and multidrug resistance frequently occur. Underlying mechanisms are multifaceted and extensively studied. In recent research, it became evident, that the lysosome is of importance in drug resistance phenotypes. While it has long been considered just as cellular waste bag, it is now widely known that lysosomes play an important role in important cellular signaling processes and are in the focus of cancer research. In that regard lysosomes are now considered as so-called “drug safe-houses” in which chemotherapeutics are trapped passively by diffusion or actively by lysosomal P-glycoprotein activity, which prevents them from reaching their intracellular targets. Furthermore, alterations in lysosome to nucleus signaling by the transcription factor EB (TFEB) – mTORC1 axis are implicated in development of chemoresistance. The identification of lysosomes as essential players in drug resistance has introduced novel strategies to overcome chemoresistance and led to innovate therapeutic approaches. This mini review gives an overview of the current state of research on the role of lysosomes in chemoresistance, summarizing underlying mechanisms and treatment strategies and critically discussing open questions and drawbacks.